Kemenparekraf's Role In Recovering The State's Economic Sector Through Tourism and MSMEs - Putri, Defi Tristio (Jurnal Mamangan, 2023)
This study aims to find out what the role of the Ministry of Tourism and Creative Economy is in helping to restore the nation's economic sector which has been devastated by the co-19 pandemic. The decline in business activities is due to the fact that people cannot carry out their lives as usual. For example, schools must be closed and transferred to online learning.. Then work becomes a work from home system or work from home to continue to follow government recommendations and help suppress the spread of Covid-19. Using a quantitative method with a constructivist paradigm and a type of case study research to see the phenomenon of the economic decline. Data retrieved via the internet and collected into one unit and then compiled and analyzed to become the results of a study. So that research uses concrete data that has validity in research. After conducting research, the Ministry of Tourism and Creative Economy played a very important role in restoring the economic sector through MSMEs. Build UMKM place for sellers small all around tourism . Government has disbursed data of IDR 123.46 trillion from PEN ( National Economic Recovery ) funds for help healing economy national. it  look from enhancement UMK contribution to PDV of 61.07% compared to right with effort big other that only give contribution of 38.93%. So that MSMEs are still Becomes buffer economy national.